PENGGUNAAN MODEL PEMBELAJARAN DISCOVERY LEARNING DALAM PEMBELAJARAN MENULIS TEKS ANEKDOT PADA PESERTA DIDIK KELAS X SMK NU SUKAGUMIWANG - Slamet Riyadi; Irfan Efendi; Ade Hasanudin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aimed to determine the effectiveness of the Discovery Learning model on the anecdote text writing skills of tenth-grade students at SMK NU Sukagumiwang. The research also sought to describe the learning activities that occurred during the implementation of this model. A quantitative approach with a quasi-experimental design was employed, involving an experimental and a control group. The sample consisted of the entire population of 64 tenth-grade students, selected through a saturated sampling technique. Data were collected using tests and observation and were statistically analyzed using descriptive statistics and an independent sample t-test with SPSS version 21.0. The results revealed a significant difference in learning outcomes. The experimental group, which used the Discovery Learning model, achieved a post-test average score of 77.5, while the control group's average was 70.3. The t-test showed a significance value of 0.000 < 0.05 and a calculated t-value (5.233) greater than the table t-value (1.998), leading to the rejection of H0 and acceptance of Ha. This confirms that the Discovery Learning model is effective. Furthermore, students in the experimental group were observed to be more active in asking questions, seeking information, and processing data to find new solutions, which fostered a more interactive and creative learning process.